تأثير رش الزنك بمستويات ومواعيد مختلفة في نمو تراكيب وراثية من زهرة الشمس وحاصلها ونوعيتها (Helianthus annuus L., Compositae) - سعد احمد محمد احمد الدوري (University of Mosul-college of Basic Education, 2014)
Because of the calcareous nature of soils in Mosul city and the high value of the soil pH, most micro nutrients have negligible availability in these soils, therefore an field experiment was conducted during two successive growing seasons 2009-2010 and 2010-2011 to determinate the response of growth, yield and quality of sunflower (Helianthus annuus L.) genotypes to different levels and timing of zinc foliar application. The experiment comprised of three levels of zinc sprayed on the plant leaves one dose (0, 7.5 and 15 mg.l-1), three sunflower genotypes (Manon, Fodak and Sunbred) and three timing of zinc application (heading stage, flowering stage and seed filling stage). It was conducted according to Randomized Completely Block Design with split - split plot with three replications. The results could be summarized as: The addition of zinc sprayed on the plant leaves with concentration 7.5 mg.l-1 led to an significant increase in characteristics: plant height, leaf area, number of seeds.head-1, weight of thousand seed, seed yield per plant, total seed yield, seed oil content, seed protein content and oil yield, protein yield, while increasing concentration of zinc to 15 mg.l-1cause a significant decrease in all investigated characteristics in the two growing seasons. Fodak genotype gave a high mean for characters: plant height, stem diameter, leaf area, number of seeds.head-1, seed yield per plant, total seed yield, seed oil content, seed protein content, oil yield and protein yield in both seasons 2009-2010 and 2010-2011. Delaying timing of zinc foliar application to flowering stage causes an significant increase of all investigated characteristics in both seasons 2009-2010 and 2010-2011.